PHYSICOCHEMICAL, FORMULATION, AND EVALUATION OF ANTIFUNGAL HERBAL SOAP USING CURCUMA AMADA ROXBURGH AND PRUNUS DULCIS - C, HARI PRASATH; S, DIVYAPRIYA; KUMAR V, DHANA RANGESH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Mango ginger (Curcuma amada Roxburgh) belongs to the Zingiberaceae family, a type of annual plant. It is commonly used for culinary and therapeutic purposes, which also has the maximum amount of health benefits. The main objective of the study is formulation of antifungal herbal soap which is alternate to chemical products. Methods: In the present study, aqueous, ethanol, and chloroform extract of mango ginger were subjected to qualitative and quantitative phytochemical analysis and determined the antioxidant activity using DPPH assay and FRAP assay. Furthermore, the ash and moisture content of the rhizome was analyzed. The aqueous extract of mango ginger is used in the GC-MS study to identify the compounds present in the mango ginger. The oil was extracted from mango ginger and subjected to antifungal activity by the well-diffusion method against three fungi, namely, Candida tropicalis, Candida auris, and Candida albicans. Using the extracted mango ginger oil and almond oil, antifungal Herbal Soap is formulated. Result: This study shows that aqueous extract of mango ginger has a greater number of carbohydrates, phenol, flavonoids, and antioxidant activity than other extracts. Antifungal activity is observed at various concentrations of extract, which shows that the highest zone of inhibition is 1.4 cm for C. auris. The formulated soap has a good aroma, and color – mustard yellow. This soap is base in nature and its pH is 8.9. Conclusion: According to the above studies, the formulated antifungal herbal soap may rectify the problems of fungal skin infections.